1992
DOI: 10.1159/000247524
|View full text |Cite
|
Sign up to set email alerts
|

Acute Generalized Exanthematic Pustulosis Induced by Cefaclor and Acetazolamide

Abstract: We report a case of acute generalized exanthematic pustulosis induced by 2 different drugs, cefaclor and acetazolamide. The diagnosis was confirmed by challenge tests, and these 2 drugs respectively were proven to be responsible for the patient’s pustular eruptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 2 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…There are only two reports on positive-Dl.ST in AGEP (4, 5); negative results have been reported by several authors (3,7,8). Triibe and Burg reported a case of AGEP due to doxycycline, in which DLST showed a very high stimulating index of 13 (5).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…There are only two reports on positive-Dl.ST in AGEP (4, 5); negative results have been reported by several authors (3,7,8). Triibe and Burg reported a case of AGEP due to doxycycline, in which DLST showed a very high stimulating index of 13 (5).…”
Section: Discussionmentioning
confidence: 83%
“…While provocation tests are most reliable for identifying the causative drugs, they are sometimes potentially dangerous. In AGEP, the diagnosis of drug eruption is occasionally made by programmed or accidental provocation tests (2)(3)(4)(5). Both patch tests and drug lymphocyte stimulation tests (DLST) have been useful in correlating a specific drug with AGEP (2,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few cases of CADR with oral acetazolamide have been previously reported [5,6,7](table 3). All these cases were severe CADR (AGEP, Stevens-Johnson syndrome).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in the treatment for glaucoma and is also recommended for the prophylaxis of acute mountain sickness (3). Recently Ogoshi et al (4) reported a case of an acute generalized exanthematic pustulosis (AGEP), which occurred following administration of acetazolamide for glaucoma. The pustular eruptions precipitated by acetazolamide in our case may be atypical, because they had no relationship to preexisting psoriatic lesions.…”
Section: Discussionmentioning
confidence: 99%